A simple molecular technique for distinguishing species reveals frequent misidentification of Hawaiian corals in the genus Pocillopora - Erika C. Johnston; Zac H. Forsman; Robert J. Toonen (PeerJ, 2018)
Species within the scleractinian genus Pocillopora Lamarck 1816 exhibit extreme phenotypic plasticity, making identification based on morphology difficult. However, the mitochondrial open reading frame (mtORF) marker provides a useful genetic tool for identification of most species in this genus, with a notable exception of P. eydouxi and P. meandrina. Based on recent genomic work, we present a quick and simple, gel-based restriction fragment length polymorphism (RFLP) method for the identification of all six Pocillopora species occurring in Hawai‘i by amplifying either the mtORF region, a newly discovered histone region, or both, and then using the restriction enzymes targeting diagnostic sequences we unambiguously identify each species. Using this approach, we documented frequent misidentification of Pocillopora species based on colony morphology. We found that P. acuta colonies are frequently mistakenly identified as P. damicornis in Kāne‘ohe Bay, O‘ahu. We also found that P. meandrina likely has a northern range limit in the Northwest Hawaiian Islands, above which P. ligulata was regularly mistaken for P. meandrina.